Occurrence and Dietary Exposure to Acrylamide from Foods Consumed within and outside Main Meals in Singapore - Wesley Zongrong Yu; Ping Shen; Ignatius Lim; Raymond Rong Sheng Shi; Miaohua Cai; Yee Soon Chin; Ai Jin Tay; Wei Min Ang; Jun Cheng Er; Geraldine Songlen Lim; Yuansheng Wu; Angela Li; et al. (Foods, 2023)
This study investigated the influence of ‘snackification’ in Singaporean diets, leading to increased dietary acrylamide exposure. Acrylamide concentrations in commonly consumed foods within and outside the main meals were measured using liquid chromatography with tandem mass spectrometry (LC-MS/MS). High acrylamide concentrations were detected in vegetables cooked at high temperatures (ranging from 0.5 to 478.4 µg/kg) and potato-based crackers and chips (ranging from 81.8 to 2095.8 µg/kg). The estimated total dietary exposure for the Singapore population was 0.165 µg/kg bw/day for general consumers and 0.392 µg/kg bw/day for high consumers (95th percentile). The acrylamide exposure from outside main meals was nearly equivalent to that from within the main meals. The calculated margins of exposure (MOE) were below 10,000, indicating potential human health concern. These findings highlight the need for industry practices and consumer advisories to reduce acrylamide exposure from foods consumed both within and outside main meals.